Reduction of work in process and manufacturing lead time using value stream mapping in the medical industry - Nor Najwafatima, Yusaini (2023)
The company must reduce inventories, increase efficiency, and lower manufacturing lead times to maintain consumer satisfaction in the face of increased product competition. Anything that does not add any value to the product and reduces the effectiveness ofthe process is referred to as "waste." The company will suffer several consequences as a result of waste, including an increase in production costs as a result of the requirement for additional space and handling, the accumulation of work-in-progress piles between workstations as a result of delays, and an increase in the number of redundant operations as a result of overprocessing. This project is a case study of a medical company dealing with long manufacturing lead times and a large amount of work in progress (WIP). The goal of the project is to reduce manufacturing lead time and the number of items in progress, thereby reducing waste on the production floor (WlP). Value Stream Mapping (VSM) will be used to identify waste by distinguishing value-added activities from non-value-added activities in the manufacturing process. The analysis is carried out using the lean tool value stream mapping to improve the medical production line. The current VSM is developed, and wastes are found by examining the existing production line. VSM will most likely execute manufacturing in the future by removing identified wastes. Lead time is reduced by removing waste, and WIP may be reduced as well. As a result, the consumer receives more value at a reduced cost. This finally leads to getting a competitive advantage in an already competitive market. To solve the difficulties, future state maps were constructed using lean techniques and kaizen. Excess inventory is eliminated, and total cycle time and inventory time at various stations are reduced. The future state map illustrates an increase in processes of 87.5% and an increase in value-added activities of39%, resulting in a 46.9% reduction in manufacturing lead times.